THE SUBJECTIVE SIDE OF SMUGGLING - Šaforostovs, Aleksejs (Administrative and Criminal Justice, 2016)
The aim of the article is the study of the subjective side of smuggling, as a kind of shadow economy. Understanding the subjective side of contraband in the existing legislative acts of the Republic of Latvia and the response of the state for illegal actions does not fully meet the targets for reduction of the shadow economy, and requires more detailed study, especially in the subjective part of smuggling. Article novity shown as an expanded understanding of the subjective side comparison of smuggling in Latvia and other countries. A wide range of international experience and analysis of the regulatory framework helps to make conclusions about the direction of the correction in the understanding of the subjective side of smuggling today. Summing up the conclusions of the article and by the author's made proposals it can be said, that they will undoubtedly provide a more precise understanding of the weaknesses of the subjective side of contraband in the Latvian legislation and identify possible ways to improve the regulatory framework of the subjective side of such action as smuggling.